Percepções parentais sobre educação sexual: continuidades e rupturas entre gerações - Gonçalves, Clara Isabelel das Neves (Universidade Federal de São Carlos, 2025)
For more than a century, there have been intense debates about sex education (SE) due to differences in people’s understanding of the effects of different SE strategies to achieve goals such as protection, dissemination of information, and promotion of sexual well-being.This study investigated parents’ perceptions of the sex education they received and its relationship with the educational practices they adopt with their own children, analyzing generational continuities and changes. Although academic literature recognizes the family's role in shaping sexuality, there is still a scarcity of research in Brazil that places the family system at the center of analysis - particularly regarding the intergenerational transmission of information and values related to sexuality. The study employed a quantitative-qualitative, cross-sectional, descriptive, and correlational design. A total of 64 individuals (45 mothers and 19 fathers) born between 1950 and 2000, all with at least a high school education, participated in the study. Data were collected using an online questionnaire developed by the author, composed of both closed and open-ended questions. The results indicate that many participants received insufficient guidance during their upbringing and that their families were minimally involved in their sex education. Despite this, there was a clear desire to provide their children with a different and more adequate form of sex education, although some participants reported feeling unprepared for this task. A significant association was found between having received (or not received) information in the family of origin, and the tendency to pass these ideas on to their own children (X²(1) = 16.295; p < 0.001). It was also observed that younger parents tended to use the internet more frequently as a source of information and, in some cases, had arranged consultations with healthcare professionals to address this topic with their children. However, the educational practices reported revealed a predominance of biomedical content, to the detriment of a broader approach to sexuality. The results highlight the need to develop resources to help parents engage in their children’s sexual education with greater autonomy and critical awareness, promoting an emancipatory approach to sex education grounded in citizenship and human rights. A key limitation of the study concerns the sample, which is not representative of the Brazilian population of parents. In addition to being individuals more open to discussing sexuality, most participants had high levels of education and were over 45 years old, which limits the analysis of broader historical-cultural influences. Based on these results, it would be useful to develop and evaluate materials to assist parents in reflecting on and preparing to address sex education with their children in a continuous and comprehensive manner, taking into consideration the different stages of child and adolescent development
Parental perceptions regarding sexual education: continuity and change across generations
Keywords: Educação sexual; Parentalidade; Transmissão intergeracional; Família; Crianças; Adolescentes; Sex education; Parenting; Intergenerational transmission; Family; Children; Adolescents; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS